2021
DOI: 10.1021/acs.jpcb.1c05793
|View full text |Cite
|
Sign up to set email alerts
|

NaFSI and NaTFSI Solutions in Ether Solvents from Monoglyme to Poly(ethylene oxide)—A Molecular Dynamics Study

Abstract: Classical molecular dynamics simulations have been performed for a series of electrolytes based on sodium bis(fluorosulfonyl)imide or sodium bis(trifluoromethylsulfonyl)imide salts and monoglyme, tetraglyme, and poly(ethylene oxide) as solvents. Structural properties have been assessed through the analysis of coordination numbers and binding patterns. Residence times for Na–O interactions have been used to investigate the stability of solvation shells. Diffusion coefficients of ions and electrical conductivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Anions as the competitor against solvents interact with cations and usually impede their motions. , It is found that PS anions with shorter chains (S 4 2– ) diffuse faster than longer ones (S 6 2– and S 8 2– ), which agrees with the Stokes–Einstein relation. The diffusion coefficients of Li + in corresponding electrolytes follow the same order on account of their strong association with PS anions (Figure a). , Given the association between cations and anions, diffusion modes change with the interaction strength of these two species. ,, According to the study of Self et al, the larger binding energy of Li + –BF 4 – than Li + –PF 6 – makes Li + diffuse with BF 4 – and PF 6 – via the vehicular and structural mechanisms, respectively (Figure b) . In addition, the Li + transport in LiBF 4 and LiPF 6 shifts contrarily as the salt concentration increases.…”
Section: Physicochemical Properties Of Electrolytesmentioning
confidence: 86%
See 1 more Smart Citation
“…Anions as the competitor against solvents interact with cations and usually impede their motions. , It is found that PS anions with shorter chains (S 4 2– ) diffuse faster than longer ones (S 6 2– and S 8 2– ), which agrees with the Stokes–Einstein relation. The diffusion coefficients of Li + in corresponding electrolytes follow the same order on account of their strong association with PS anions (Figure a). , Given the association between cations and anions, diffusion modes change with the interaction strength of these two species. ,, According to the study of Self et al, the larger binding energy of Li + –BF 4 – than Li + –PF 6 – makes Li + diffuse with BF 4 – and PF 6 – via the vehicular and structural mechanisms, respectively (Figure b) . In addition, the Li + transport in LiBF 4 and LiPF 6 shifts contrarily as the salt concentration increases.…”
Section: Physicochemical Properties Of Electrolytesmentioning
confidence: 86%
“…101,412 Given the association between cations and anions, diffusion modes change with the interaction strength of these two species. 396,413,414 According to the study of Self et al, the larger binding energy of Li + −BF 4 − than Li + −PF 6 − makes Li + diffuse with BF 4 − and PF 6 − via the vehicular and structural mechanisms, respectively (Figure 20b). 105 In addition, the Li + transport in LiBF 4 and LiPF 6 shifts contrarily as the salt concentration increases.…”
Section: Ionic Transportmentioning
confidence: 99%
“…The electrolytes are prepared by mixing a suitable sodium salt in a single or mix of organic ether or ester-based solvents with occasional use of additives. NaPF 6 and NaClO 4 are the most widely used salts for SIBs with sporadic use of the salts such as sodium bis(fluorosulfonyl)imide (NaFSI) [103], sodium bis(trifluoromethylsulfonyl)imide (NaTFSI), and NaCF 3 SO 3 [104]. Ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), propylene carbonate (PC), dimethyl ether (DME), tetraethylene glycol dimethyl ether (TEGDME), and diethylene glycol dimethyl ether (DEGDME) are some of the most commonly used solvents reported in the literature [56].…”
Section: Sei Layer and Its Impact On Icementioning
confidence: 99%
“…The average coordination number (CN) calculated for the P(EO) 24 :Na + SPEs is 4.7 ± 0.3 whereas that for the P(EO) 4 :Na + SPEs is 3.5 ± 0.1 which is good agreement with recent molecular dynamics simulations on PEO−NaFSI mixtures at similar concentrations. 62 To obtain further mechanistic insight into the effect of h-BN on the SPE solvation environment, we carried out DFT calculations to determine the pairwise binding energies of various intercomponent interactions as shown in Figure 4. These interactions include NaFSI salt binding, PEO−cation (Na + ) binding in a systematic incremental coordination number from 2 to 6, and the interaction(s) of h-BN with a fully dissociated cation and anion as well as with a single PEO unit.…”
Section: Solvation Structure and Dft Calculationsmentioning
confidence: 99%